the development of a newly designed building performance survey framework for energy efficient building: a review - Ban, Huat Ng; Akasah, Zainal Abidin (2013)
There exists a well-known gap between occupants and building’s energy-efficient designs. A comprehensive building performance diagnostic technique, Post Occupancy Evaluation (POE) may surpass the current evaluation method and reduce the gap between occupants and building’s energy-efficient design. For these reasons, the aim of this research is to develop a framework for the identification of problems in respect to energy-efficient design which affecting occupants’ comfort. The objectives of this research are to determine the energy-efficient building in Malaysia, to identify the effects of energy-efficient design problems towards occupants’ comfort, and to propose a holistic occupant survey framework for the rating of energyefficient design problems which affecting the occupants’ comfort. This research will be conducted in energy-efficient buildings in Malaysia. A new building performance survey framework will be constructed and tested on the selected energy-efficient building. The tested result will be analyzed using Statistical Package for Social Science (SPSS) in order to determine its reliability and validity. The research outcome shall contribute to the development of energy-efficient building through the identification of inefficient performance of the current building. Thus the newly designed building performance survey framework will be able to improve the occupants’ comfort of energy-efficient building in the future.